A protein elicitor PeVn1 from Verticillium nonalfalfae HW recognized as a MAMP triggers plant immunity response - Zhang, Ziyu; Wang, Dong; Dong, Baozhu; Wang, Yu; Xu, Jialu; Hao, Jianxiu; Zhou, Hongyou (Frontiers in Plant Science, 2024)
Protein elicitors can induce plant systemic resistance to pathogens. The recognition of a potential elicitor activates intracellular signaling events, leading to plant resistance against pathogens. In this study, a novel protein elicitor was isolated from the culture filtrate of Verticillium nonalfalfae and named PeVn1, which can induce cell death in several plant species. The PeVn1 gene was then cloned and expressed in Escherichia coli. The recombinant protein PeVn1 triggers cell death in Nicotiana benthamiana in NbBAK1 and NbSOBIR1 dependent manner. Through bioassay analysis showed that the recombinant PeVn1 induced early defense induction events, such as reactive oxygen species burst, callose deposition and the activation of defence hormone signalling pathways and defense enzyme activities. Moreover, PeVn1 significantly enhanced resistance of Nicotiana benthamiana to Sclerotinia sclerotiorum, Botrytis cinerea and N. benthamiana mosaic virus and tomato to Pseudomonas syringae pv. Tomato DC3000. In conclusion, our study reveals that PeVn1 protein as a microbe-associated molecular pattern can induce plant immune responses, which provides a theoretical basis for the development of novel protein-induced disease resistance agents.